Design of spherically structured 3D in vitro tumor models -Advances and prospects. (15th July 2018) - Ferreira, L.P.; Gaspar, V.M.; Mano, J.F.
Graphical abstract: Abstract: Three-dimensional multicellular tumor models are receiving an ever-growing focus as preclinical drug-screening platforms due to their potential to recapitulate major physiological features of human tumors in vitro . In line with this momentum, the technologies for assembly of 3D microtumors are rapidly evolving towards a comprehensive inclusion of tumor microenvironment elements. Customized spherically structured platforms, including microparticles and microcapsules, provide a robust and scalable technology to imprint unique biomolecular tumor microenvironment hallmarks into 3D in vitro models. Herein, a comprehensive overview of novel advances on the integration of tumor-ECM components and biomechanical cues into 3D in vitro models assembled in spherical shaped platforms is provided. Future improvements regarding spatiotemporal/mechanical adaptability, and degradability, during microtumors in vitro 3D culture are also critically discussed considering the realistic potential of these platforms to mimic the dynamic tumor microenvironment. From a global perspective, the production of 3D multicellular spheroids with tumor ECM components included in spherical models will unlock their potential to be used in high-throughput screening of therapeutic compounds. It is envisioned, in a near future, that a combination of spherically structured 3D microtumor models with other advanced microfluidic technologies will properly recapitulate the flow dynamics of human tumors in vitro . Statement of Significance: The ability to correctly mimic the complexity of the tumor microenvironment in vitro is a key aspect for the development of evermore realistic in vitro models for drug-screening and fundamental cancer biology studies. In this regard, conventional spheroid-based 3D tumor models, combined with spherically structured biomaterials, opens the opportunity to precisely recapitulate complex cell-extracellular matrix interactions and tumor compartmentalization. This review provides an in-depth focus on current developments regarding spherically structured scaffolds engineered into in vitro 3D tumor models, and discusses future advances toward all-encompassing platforms that may provide an improved in vitro/in vivo correlation in a foreseeable future.